The use of intradetrusor botulinum toxin in the geriatric population - William Chui; Alvaro Bazo; Henry H. Yao; Joshua Kealey; Lana Pepdjonovic; Helen E. O'Connell; Johan Gani; Richard Parkinson (BJUI Compass)
Abstract Objectives This study aims to explore the impact of age on long‐term outcomes associated with intradetrusor botulinum toxin (BoNT) usage (up to four cycles) in elderly patients with refractory overactive bladder syndrome (OAB). Materials and Methods We conducted a retrospective observational cohort study across institutions in Nottingham (UK) and Melbourne (Australia). Patients with refractory OAB and treated with intradetrusor BoNT between January 2005 and January 2020 were stratified into age groups: ≤40, 40–49, 50–59, 60–69 and ≥70 years. Efficacy was defined as patient self‐reported improvement in symptoms post‐BoNT injection. Duration of effect was time (months) between BoNT injection to patient reported onset of symptom recurrence. Data on BoNT type and dosing, urinary tract infection (UTI), urinary retention, ICIQ‐OAB and International Consultation on Incontinence Questionnaire Urinary Incontinence (ICIQ‐UI) questionnaires were also collected. Statistical analyses were conducted with SPSS® 25 software. P‐value < 0.05 was considered statistically significant. Results There were 943 patients stratified into age groups: < 40 (183), 40–49 (150), 50–59 (173), 60–69 (219) and ≥ 70 (218). Median age was 58 (IQR 44–69). Most patients were female 724/943 (76.8%). From Cycles 1 to 4, age group ≥ 70 efficacy rates were 85.1%, 84.1%, 92.6% and 89.3%. Corresponding median duration of effect (months) were 6.8, 8.0, 7.0 and 8.0. For Cycle 2; age ≥ 70 was a predictor of reduced efficacy (P = 0.004). Neurogenic causes of OAB were predictors of increased efficacy for Cycles 2 (P = 0.004) and 3 (P = 0.0145). Men had higher rates of urinary retention than women in Cycles 1 (42.4% vs 29.3%, P = 0.003) and 2 (37.9% vs 23.0%, P = 0.0018). All age groups showed improvement in patient‐reported outcome measures (PROMs) post‐BoNT injection. Conclusion In elderly patients with refractory OAB and treated with intradetrusor BoNT (up to four cycles), age ≥ 70 was an independent predictor for reduced BoNT efficacy (84.1%) in Cycle 2.